Redescription of Raphidascaris gigi Fujita, 1928 (Nematoda: Anisakidae), a parasite of freshwater fishes in Japan - Moravec, Frantisek; Nagasawa, Kazuya (Systematic parasitology, 2002)
A redescription is given of Raphidascaris gigi Fujita, 1928 based on newly collected specimens from the intestine of masu salmon Oncorhynchus masou (Brevoort) in the Kinu River in Japan. The species is characterised by the absence of interlabia and lateral alae, by the presence of lips without lateral membranous flanges and by numerous pre-anal and postanal papillae in the male. Although the general morphology of this species resembles that of Ichthyascaris spp. as defined by Bruce (1990), who transferred R. biwakoensis (= R. gigi) to this genus, the absence of the alae uniting close the ventrolateral lips shows clearly that it belongs to Raphidascaris Railliet & Henry, 1915. Ichthyascaris Wu, 1949 is here considered a subgenus of Raphidascaris, and two species described in the former genus are transferred to the latter as R. gymnocraniae (Bruce, 1990) n. comb. and R. sillagoides (Bruce, 1990) n. comb. The finding of R. gigi in O. masou represents a new host record.
Keywords: Animals; Intestines; Nematoda; střeva; mikroskopie elektronová rastrovací; Female; Japan; mužské pohlaví; zvířata; hlístice; Oncorhynchus; Male; Microscopy, Electron, Scanning; ženské pohlaví; Japonsko